Open/Distance Teaching Universities Worldwide: Current Challenges and Future Prospects - Sarah Guri-Rosenblit (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
This article examines the current challenges faced by open/distance teaching universities worldwide. The challenges relate to: the change of technological and instructional infrastructures; the move from national systems to a global landscape; the need to find appropriate parties for collaboration in the academic and corporate worlds; the search for quality assurance mechanisms; and the digital divide between developing and developed countries, and between poor and rich. The article concludes with highlighting the leading prospects for open/ distance teaching universities.